A comprehensive study on image steganography and steganalysis techniques. (2015) - Amsaveni, A.; Vanathi, P.T.
In this modern era, computers and the internet are major communication media that connect different parts of the world. The advancement in the field of data communication has hiked the fear of getting the data snooped at the time of sending it from the sender to the receiver. Hence, information security becomes an inseparable part of data communication. Steganography and steganalysis are important topics in information hiding. Using steganography, information can be hidden in different embedding media, known as carriers. These carriers can be images, audio files, video files, and text files. This paper intends to give an overview of image steganographic techniques. It also attempts to identify the requirements of a good steganographic algorithm. In this paper, steganalysis, which is the science of attacking steganography, has also been discussed.